Effects of potential risk factors on the development of cardiometabolic multimorbidity and mortality among the elders in China - Zhang, Huihui; Duan, Xinyu; Rong, Peixi; Dang, Yusong; Yan, Mingxin; Zhao, Yaling; Chen, Fangyao; Zhou, Jing; Chen, Yulong; Wang, Duolao; Pei, Leilei (Frontiers in Cardiovascular Medicine, 2022)
Objectives: To examine the impact of demographic, socioeconomic, and behavioural factors on the development of cardiometabolic multimorbidity and mortality in China elders. Methods: Data from Chinese Longitudinal Healthy Longevity Survey 2002-2018 was used in the study. The outcomes included 3 states of first cardiometabolic disease, cardiometabolic multimorbidity, and all-cause mortality, and 5 possible transitions between the three states. Cardiometabolic multimorbidity was defined as at least two of hypertension, diabetes, heart disease, stroke, or cardiovascular disease. Cox regression model and multi-state Markov model were developed to evaluate the association of study factors with the progression of cardiometabolic conditions and mortality. Results: Of the 13933 eligible individuals, 7917 (56.8%) were female, and 9540 (68.50%) were over 80 years old. 2766 (19.9%) participants had first cardiometabolic disease, 975 (7.0%) participants suffered from cardiometabolic multimorbidity, and 9365 (67.2%) participants died. The progression to cardiometabolic multimorbidity was positively associated with the females (1.42; 95%CI, 1.10-1.85), living in city (1.41; 95%CI, 1.04-1.93), overweight (1.43; 95%CI, 1.08-1.90), and obesity (1.75; 95% CI, 1.03-2.98). Higher risk for first cardiometabolic disease was associated with the females (1.26; 95% CI, 1.15-1.39), higher SES (1.17; 95%CI, 1.07-1.28), no regular physical activity (1.13; 95%CI, 1.04-1.23), smoking (1.20; 95%CI, 1.08-1.33), ≤5h sleep time (1.15; 95%CI, 1.02-1.30), overweight (1.48; 95% CI, 1.32-1.66), and obesity (1.34; 95%CI, 1.06-1.69). It also should be noted that not in marriage, lower SES, and unhealthy behavioral patterns were risk factors for mortality. Conclusion: This study emphasized the importance of lifestyle and SES factors in tackling the development of cardiometabolic conditions among China elders, which could guide policy-makers to develop a tailored stage-specific intervention strategy.